2019
DOI: 10.3389/fonc.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyoma Viral Load and Intratumoral CD8+ Lymphocyte Infiltration Predict Overall Survival in Patients With Merkel Cell Carcinoma

Abstract: Introduction: Merkel cell carcinoma (MCC) is linked to the presence of clonally integrated Merkel cell polyomavirus (MCPyV) in up to 80% of the cases. The aim of the study was to determine the prognostic value of baseline MCPyV viral load and lymphocytic infiltration.Methods: MCPyV DNA prevalence, integration status and viral load were determined by specific quantitative real-time PCR in surgical specimens obtained from 49 patients with MCC treated with (n = 22, 45%) or without postoperative radiotherapy (RT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…Findings reported by Micevic et al [ 15 ] suggest that the hypomethylation of PD-L1 (and possible subsequent increased protein expression of PD-L1) is associated with a phenotype of immune activation and expression of interferon signaling pathway genes in cutaneous melanoma. This hypothesis needs further investigations in MCC patients, because some studies did not confirm the significant prognostic impact of PD-L1 on survival in MCC patients [ 2 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings reported by Micevic et al [ 15 ] suggest that the hypomethylation of PD-L1 (and possible subsequent increased protein expression of PD-L1) is associated with a phenotype of immune activation and expression of interferon signaling pathway genes in cutaneous melanoma. This hypothesis needs further investigations in MCC patients, because some studies did not confirm the significant prognostic impact of PD-L1 on survival in MCC patients [ 2 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies suggest that intratumoral CD8+ lymphocytes are strongly correlated with better survival in MCC [ 2 , 3 , 4 , 28 ]. The findings of our study confirmed that high intratumoral CD8+ cell count had a positive prognostic impact on survival in MCC patients and highlighted the crucial role of cytotoxic CD8+ lymphocytes in controlling disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако J. von der Grün и соавт. [61] не удалось выявить существенной корреляции между инфильтрацией опухоли CD8-позитивными лимфоцитами, экспрессией в опухоли PD-L1 и вирусной нагрузкой. Авторы объясняют это тем, что иммунный ответ может зависеть от механизмов, отличных от вирусной инфекции, например, от мутаций, вызванных ультрафиолетовым излучением.…”
Section: подходы к терапииunclassified